TINGKAH LAKU HARIAN KUSKUS BERUANG (Ailurops ursinus) DI CAGAR ALAM TANGKOKO BATU ANGUS - Talumepa, Pratiwi A.A.; Wungow, R. S. H.; Poli, Z.; Rimbing, S. C. (Universitas Sam Ratulangi, 2016)
DAILY BEHAVIOUR OF SULAWESI BEAR CUSCUS (Ailurops ursinus) IN TANGKOKO BATU ANGUS NATURE RESERVE. This study aimed to describe dailly behaviour of Sulawesi Bear Cuscus (Ailurops ursinus) in Tangkoko Batu Angus Nature Reserve. This reseach is expected to provide information about inactive, foraging, intake, groom and social behavior of Ailurops ursinus as primary behavior variables of the animal daily activities. The usie of vegetation during animal daily activities were introducted in this research as a secondary variable. This research used obsevation as research method and instantinous animal sampling technique. This method observed Ailurops ursinus behavior three times per day . Each single observe was done in 60 minutes with 60 seconds time interval. Every single observe was replicated 14 times. The result of this research showed that the daily behaviour of Ailurops ursinus was dominated by inactive behaviour with 56.86 percents consisted of 30.5 minutes were spent in the morning, 42.6 minutes at noon and 29.2 minutes in the afternoon. Intake behaviour took times of 26.98 percents consisted of 17.2 minutes were spent in the morning, 8 minutes at noon and 23.3 minutes in the afternoon. The foraging behaviour took times of 15.11 percents consisted of 11.7 minutes were spent in the morning, 8.7 minutes at noon and 6.6 minutes in the afternoon. Groom activity spent times of 0.98% consisted of 0.5 minutes spent in the morning, 0.5 minutes at noon and 0.7 minutes in the afternoon. Social behaviour took spent time of 0.03% of total daily behaviour spent only at noon. Keywords : Daily behaviour, Sulawesi Bear Cuscus (Ailurops ursinus), Tangkoko Batu Angus Nature Reserve